Pendidikan Islam Dalam Perprektif Ilmunya Kuntowijoyo - Eko Sumadi (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2018)
This article discussed the idea of Islam as the science of Kuntowijoyo, as well as trying to see the contribution of the idea in the context of the renewal of Islamic education. Similarly, the idea of Islamization of Science in responding to the hegemony of